Nutritional values and cooking quality of defatted kenaf seeds yellow (DKSY) noodles - Zawawi, Norhasnida; Gangadharan, P.; Ahma Zaini, R.; Samsudin, Muhamad Gaddafi; Karim, Roselina; Ismail, Maznah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
Kenaf (Hibiscus cannabinus) seeds have always being wasted as agricultural waste. Recent studies revealed that the seeds contain high fiber. The purpose of this study is to develop defatted kenaf seeds yellow noodles (DKSY) and assess the nutritional and physicohemical properties of the noodles. Defatted kenaf flour at 25% and 75% were used to make DKSY noodles and compared to wheat yellow noodles (Control). Fresh DKSY noodles were analyzed for their nutritional and physiochemical properties. The ash and fiber contents increased in order of Control > 25% DKSY > 75% DKSY noodles. While total phenolic contents (TPC) was found to be higher in 75% DKSY noodles (138.30 ± 1.63 mg GAE/100 g) than Control noodles. Colour (L, b) and hardness decreased in order of Control > 25% DKSY > 75% DKSY indicating that DKSY noodles developed less quality than Control noodles. However, cooking loss values were found to be in the same order while cooking values exist in the opposite order indicating that. DKSY noodles have better noodle cooking quality. In conclusion, nutritional properties and noodle cooking quality of yellow noodles increased with higher concentration of defatted kenaf flour but the physicochemical properties were compromised. More research needs to be done in order to develop a formulation that can increase all of the attributes studied.